The rise and fall of the mangrove forests in Maputo Bay, Mozambique - de Boer, W.F. (Wetlands ecology and management, 2002)
The change in area of mangrove forests since 1958 in Maputo Bay,Mozambique was studied. Around Maputo, a 44% reduction of the area was linkedtodifferences in accessibility, the areas closest to Maputo suffering most. Butsurprisingly, large expansions of mangrove forest were also observed. Thisincrease in area (+ 13%) was accompanied by an increase in tree cover from55 to 70%. The overall effect of mangrove forest reduction and growth resultedin a mean decrease of only 8%. The causes of the increase in mangrove area onInhaca island are discussed, and two possible factors are suggested: a changeinsedimentation and an increase in temperature. Sandbanks have increased atInhacaIsland, but no data are available for the other areas. An increase in sea andair temperature has also been noted by other authors and could explain thegrowth of the forests, which are situated at the southernmost limit of theirnormal distribution.[PUBLICATION ABSTRACT]